2007
DOI: 10.1007/s00442-007-0724-0
|View full text |Cite
|
Sign up to set email alerts
|

Environmental effects on sexual size dimorphism of a seed-feeding beetle

Abstract: Sexual size dimorphism is widespread in animals but varies considerably among species and among populations within species. Much of this variation is assumed to be due to variance in selection on males versus females. However, environmental variables could affect the development of females and males differently, generating variation in dimorphism. Here we use a factorial experimental design to simultaneously examine the effects of rearing host and temperature on sexual dimorphism of the seed beetle, Callosobru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
95
1
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 95 publications
(103 citation statements)
references
References 48 publications
5
95
1
2
Order By: Relevance
“…No sexual size dimorphism was found for P. cultellatus either (females, 0.31 Ϯ 0.03 mm, N ϭ 28; males, 0.29 Ϯ 0.03 mm, N ϭ 49; unpublished data). The sexual size dimorphism in arthropods is a result of additional larval instars, longer developmental periods, or higher growth rate in the largest sex (Esperck andTammaru 2006, Stillwell andFox 2007), although it is dependent on temperature and food quality (Parker andJohnston 2006, Stillwell andFox 2007). In the genus Pseudacteon, it is proposed that body size is determined by the host size .…”
Section: Discussionmentioning
confidence: 98%
“…No sexual size dimorphism was found for P. cultellatus either (females, 0.31 Ϯ 0.03 mm, N ϭ 28; males, 0.29 Ϯ 0.03 mm, N ϭ 49; unpublished data). The sexual size dimorphism in arthropods is a result of additional larval instars, longer developmental periods, or higher growth rate in the largest sex (Esperck andTammaru 2006, Stillwell andFox 2007), although it is dependent on temperature and food quality (Parker andJohnston 2006, Stillwell andFox 2007). In the genus Pseudacteon, it is proposed that body size is determined by the host size .…”
Section: Discussionmentioning
confidence: 98%
“…Much of this variation is genetically based and likely due to variation in selection, primarily sexual selection, among species/populations (50, 51). However, recent studies have shown that a considerable amount of intraspecific variation in SSD may be due to differences in phenotypic plasticity between males and females (51, 114, 115, 126). In this review, we examine how sex differences in phenotypic plasticity affect patterns of SSD in insects.…”
Section: Introductionmentioning
confidence: 99%
“…Variation in SSD can result when males and females respond differently to their environment (differential-plasticity hypothesis [18]), and this may be an important contributor to the observed variation in SSD. Thus the degree to which different environmental factors such as juvenile density, food quality or quantity, and temperature elicit contrasting plastic body size responses between the sexes should be informative [12,19]. Here, we specifically focus on sex-dependent differences in T-S responses, as this may ultimately help to elucidate the underlying drivers of both SSD and T-S responses.…”
Section: Introductionmentioning
confidence: 99%